The Rehabilitation and Ethnic Vetting of the Polish Population in the Voivodship of Gdańsk after World War II - Bykowska, Sylwia (2020)
This book describes the tragedy of a border society that had no place inside the boundaries of a nation-state under totalitarianism. It is the story of citizens of the former Third Reich with Polish ethnic roots in the second half of the 1940s. The story takes place in Gdańsk-Pomerania, which was a difficult homeland for its citizens. This book depicts the consequences of Third Reich’s policies on this territory and the disastrous effects of communist policy towards the indigenous population after 1945. In parallel with exchange of population, the fortunes of the indigenous population unfolded. Based on archival sources, this work presents the fate of Pomeranians and the residents of Gdańsk who had to prove their national usefulness before they joined the post-war life.